Semantic, Conceptual and Cultural validation of FRAT´s Scale for Portuguese population - Abreu, Cidalina da Conceição Ferreira de (2019)
Theme: Public Health initiatives Abreu, C.; Vaquinhas, M. e-mail: cila@esenfc.pt Coimbra Nursing School - Portugal Research Unit of Coimbra Nursing School - UICISA-E; Financed by FCT Semantic, Conceptual and Cultural validation of FRAT´s Scale for Portuguese population Background: Falls are a serious public health problem in society globally and in accordance with the Joint Declaration of the European Stakeholders Alliance for Active Ageing through Falls Prevention (2015, p. 2) "falls are a major indicator of increasing frailty and loss of independence and mobility. (...) Those residing in care or nursing settings have an even greater risk of falls and fractures". Considering Portugal, the elderly population aged 65 or over is 2.069 million people, representing around 19.9% of the total population in 2013 (INE, 2015) is alarming and it is known that it tends to increase over the years. According to this situation, falls will increase and best practice for patient safety is needed, consequently intuitional cost will diminish with falls prevention. Validation of FRAT´s Scale (Fall Risk Assessment Tool) to the Portuguese population is needed to prevent falls risk in residential nursing homes. Aim: To carry out the semantic, conceptual and cultural validation of the FRAT´s Scale for Portuguese population. Methodology: FRAT Scale is used in Victoria-Australia residential nursing homes for elderly people and it is validated for this population. For the semantic, conceptual and cultural validation of Scale and subsequent psychometric validation for the Portuguese population, the author was asked to authorize the study and it was accepted. For the first purpose, all the translation procedures mentioned in the scientific literature were carried out. This process followed five steps: Translation by two bilingual experts; Synthesis of the procedures of the two translations; Retroversion; Panel of experts; Testing of the pre-final version of the FRAT´s Scale (Ribeiro 2010; Vilelas, 2009). Results and Conclusion: It was done the semantic, conceptual and cultural validation of the FRAT´s Scale to the Portuguese population. Psychometric measurement will be done lately.